New Team Roles Typology for Organizational Context - Filipov, Dmytro (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
A new diagnostic tool has been proposed for use in modern corporations to support a wide range of problems related to the interaction of company staff in solving work tasks. This new development combines the strengths of tools already used in this field, namely, DISC and MBTI.The tool contains a description of 4 factors and 16 types based on these factors, as well as a questionnaire on 33 questions, which identifies the respondent's affiliation to the type based on the assessment of the result for each of the 4 scales. For the types, practical principles for the transition from the type to its place in the corporate organizational structure have been proposed, as well as the types are associated with commonly known archetypes for their intuitive understanding. An example of an organizational structure consisting of the proposed types has been provided, but at the same time it reflects the typical organizational structure of an economical corporation.An empirical study of the reliability for new questionnaire in a sample of more than 2,300 respondents from the Internet search engines users has been conducted. Sufficient levels (> 0.7) of Cronbach's alpha and MacDonald's omega are shown in exploratory and confirmatory factor analysis for each of the factors. The factors independence is shown as well. The proposed scales are also compared with the scales of methods for assessing emotional intelligence and creativity.Thus, the proposed typology is designed to solve a wide range of organizational tasks from building a new organization to optimizing the use of staff in existing project teams, and the work of recruitment and staff development departments.
Keywords: typology; organizational structure; MBTI; DISC; questionnaire